ANALISIS PENGARUH KUALITAS PELAYANAN E-COMMERCE SHOPEE TERHADAP KEPUASAN KONSUMEN SHOPEE INDONESIA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TRIDINANTI PALEMBANG PENGGUNA SHOPEE - Nyayu Khairani Putri; Dian Septianti; Nina Fitriana (JURNAL KOMPETITIF, 2022)
The purpose of this research is to analyze the effect of Shopee's E-Commerce service quality on Shopee Indonesia's consumer satisfaction on students of the Faculty of Economics, Tridinanti University, Palembang, Shopee users. The variables used in this study are service quality which consists of efficiency, fullfilment, reliability, privacy, responsiveness, compensation, and contacts. The population in this study ware people who had used Shopee, while the study sample was 100 respondents. Multiple Regression Analysis is a data analysis technique in this study using the IBM SPSS Statistics 22 application. The results showed that there was a significant effect of efficiency, reliability, privacy, responsiveness, and contact on customer satisfaction. On the other hand, fullfilment and compensation on customer satisfaction have no significant effect.Keywords: Service Quality and Customer Satisfaction